The Aim and Legacy of the Commission of Inquiry into Labour Legislation (Wiehahn Commission), 1977-1980 - Macqueen, Ian (University of Pretoria, 2021)
Mini Dissertation (MSocSci (History))--University of Pretoria, 2020.